2005
DOI: 10.1007/s10439-005-3236-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Conductivity on ST-Segment Epicardial Potentials Arising from Subendocardial Ischemia

Abstract: We quantify and provide biophysical explanations for some aspects of the relationship between the bidomain conductivities and ST-segment epicardial potentials that result from subendocardial ischemia. We performed computer simulations of ischemia with a realistic whole heart model. The model included a patch of subendocardial ischemic tissue of variable transmural thickness with reduced action potential amplitude. We also varied both intracellular and extracellular conductivities of the heart and the conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 10 publications
10
67
0
Order By: Relevance
“…Our results are consistent with previous modelling studies in realistic hearts [2,3] that found that the EPD assumes a different character for low, medium and high thicknesses of the ischaemic region. However, systematic studies into the effect of different fibre rotation angles and also into the effect of varying the six bidomain conductivity values in realistic geometries have not yet been performed.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous modelling studies in realistic hearts [2,3] that found that the EPD assumes a different character for low, medium and high thicknesses of the ischaemic region. However, systematic studies into the effect of different fibre rotation angles and also into the effect of varying the six bidomain conductivity values in realistic geometries have not yet been performed.…”
Section: Resultssupporting
confidence: 93%
“…slabs, cylinders, half-ellipsoids [1]), while other work uses more realistic geometries [2,3]. Another study [4] has looked at the effect of the shape of the ischaemic region on the epicardial potential distributions (EPDs) that are produced.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have used whole-heart models to explore the effects of model parameters on epicardial potentials. Hopenfeld et al [20] studied the effect of anisotropy values and transmural extent on epicardial potential patterns. Our previous study concentrated on the value of ST deviation on the epicardium directly overlying the ischemic zone [41], considering anisotropy values, transmural extent, and radius of the zone.…”
Section: Effect On Simulated Action Potentialsmentioning
confidence: 99%
“…Thus, these studies explain why ST depression could not be reproduced in animal models. They also suggest alternatives: ST depression can result if the subendocardial ischemic zone is sufficiently thin and covers a large part of the subendocardium [20,41]. This may well correspond (1) with the clinical observation of ST depression in left-main or multivessel disease, which involves ischemic zones that occupy nearly the entire left ventricular subendocardium, as witnessed by autopsy results [5,28,38]; and (2) with the typical pattern of ST depression that can be observed during a stress test and is thought to be caused by global subendocardial ischemia [12].…”
Section: Introductionmentioning
confidence: 98%
“…14,15 For such simulations we used the bidomain approach, 12 which requires intracellular and extracellular anisotropic conductivity tensors under normal conditions and under the varied influences of acute ischemia (e.g. differences in cell and capillary volumes due to accumulation of metabolic waste products and changes in the osmotic/hydrostatic pressure, as well as changes in gap junction conductivity and the rise in extracellular potassium), conditions for which there is very sparse experimental literature.…”
Section: Introductionmentioning
confidence: 99%